Women and Terrorism: An Interdisciplinary Study of Peacebuilding Education - Luq Yana Chaerunnisa; Mohammad Andi Hakim (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2023)
Women's involvement in terrorism activities has increased over the past 10 years. The role of women, which was initially as supporters of acts of terrorism, has transformed into perpetrators of terrorism. This article focuses on the factors of women's involvement in acts of terrorism as well as peace building actions to overcome it. This research is a literature research using an interdisciplinary approach. This study concludes that women's involvement in acts of terrorism is not only in the name of religion, but also due to various aspects of life such as ideological doctrine, political, economic and personal factors. Peace building efforts towards women's involvement in acts of terrorism can be a solution in tackling radicalism. The approaches needed include the deradicalization, religious and ideological, psychological, economic, socio-cultural, legal and political approach. The use of information technology and community-based approaches are also important factors in tackling this problem.